Corporations, minors, and other innocents — A reply to R. E. Ewin - Wilson, P. Eddy (Journal of business ethics, 1994)
R. E. Ewin has argued that corporations are moral persons, but Ewin describes them as being unable to think or to act in virtuous and vicious ways. Ewin thinks that their impoverished emotional life would not allow them to act in these ways. In this brief essay I want to challenge the idea that corporations cannot act virtuously. I begin by examining deficiencies in Ewin's notion of corporate personhood. I argue that he effectively reduces corporations to the status of incompetent patients. I shall make use of a richer notion of corporate personhood as I explore the logical relationship between corporate action and the quality of the corporate emotional life. After discussing an alternate methodology for making moral assessments of action I consider briefly two corporate disasters: the crash on Mt. Erebus, the Imperial Foods plant fire. These cases are used to show the inadequacy of Ewin's thesis that only corporate managers are capable of displaying vice.